Morphology of viscoplastic drop impact on viscoplastic surfaces. Issue 4 (5th December 2016) - Chen, Simeng; Bertola, Volfango
Abstract : The impact of viscoplastic drops onto viscoplastic substrates characterized by different magnitudes of the yield stress is investigated experimentally. Abstract : The impact of viscoplastic drops onto viscoplastic substrates characterized by different magnitudes of the yield stress is investigated experimentally. The interaction between viscoplastic drops and surfaces has an important application in additive manufacturing, where a fresh layer of material is deposited on a partially cured or dried layer of the same material. So far, no systematic studies on this subject have been reported in literature. The impact morphology of different drop/substrate combinations, with yield stresses ranging from 1.13 Pa to 11.7 Pa, was studied by high speed imaging for impact Weber numbers between 15 and 85. Experimental data were compared with one of the existing models for Newtonian drop impact onto liquid surfaces. Results show the magnitude of the yield stress of drop/substrate strongly affects the final shape of the impacting drop, permanently deformed at the end of impact. The comparison between experimental data and model predictions suggests the crater evolution model is only valid when predicting the evolution of the crater at sufficiently high Weber numbers.